ANALISIS APLIKASI OUTLOOK EXPRESS TERHADAP INFORMASI KERJA DI PT TANJUNG HARAPAN SENTRANUSA - Alex Darmansyah; Weni Putri; Nanda Jarti (LPPM Universitas Ibnu Sina, 2025)
Outlook Express Aplication is an application that serves to convey work information in the form of electronic mail or e-mail whether it be text, pictures and video. The purpose of the study was to find out: use outlook, To find work, and the influence of outlook express to employee information PT Tanjung Harapan. Theoretically usefulness is to determine how much information the employee in the use of Outlook Express, while the practical usefulness is expected that all parties can determine the effect resulting from Outlook Express so that employees can take advantage of the best in the business information. The study was conducted in PT Tanjung Harapan, Jl. Sekupang Industrial Estate, Batam, Indonesia. The research method used is a quantitative research method is descriptive and associative by using simple regression